Effects of propofol pretreatment on myocardial cell apoptosis and SERCA2 expression in rats with hepatic ischemia/reperfusion - Yu,Shuzhen (2018)
Abstract Introduction: Hepatic ischemia-reperfusion injury is a common pathophysiological process in liver surgery. Whether Propofol can reduce myocardial ischemia-reperfusion injury induced by hepatic ischemia-reperfusion injury in rats, together with related mechanisms, still needs further studies. Objective: To investigate if propofol would protect the myocardial cells from apoptosis with hepatic ischemia-reperfusion injury. Methods: Male Sprague-Dawley rats (n = 18) were randomly allocated into three groups: Sham Group (Group S, n = 6), Hepatic Ischemia-reperfusion Injury Group (Group IR, n = 6) and Propofol Group (Group P, n = 6). Group S was only subjected to laparotomy. Group IR was attained by ischemia for 30 min and reperfusion for 4 h. Group P was subjected identical insult as in Group IR with the administration of propofol started 10 min before ischemia with 120 mg.kg−1, following by continuous infusion at 20 mg.kg−1.h−1. Cell apoptosis was examined by terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling assay. Endoplasmic reticulum Ca2+-ATPase2 (SERCA2) and cysteine-containing aspartic acid cleaved-caspase3 (cleaved-caspase3) were assayed by western blot and Altimeter polymerase chain reaction. Results: Apoptosis rate was increased, with mRNA and protein of SERCA2 down-regulated and cleaved-caspase3 up-regulated in Group IR compared with Group S (p < 0.01). Apoptosis rate was decreased, with mRNA and protein of SERCA2 up-regulated and cleaved-caspase3 down-regulated in Group P compared with Group IR (p < 0.01). Conclusions: Propofol can reduce hepatic ischemia-reperfusion injury-induced myocardial cell apoptosis, meanwhile, can up-regulate mRNA and protein of SERCA2 in rats.